Hemokinin-1 as a Mediator of Arthritis-Related Pain via Direct Activation of Primary Sensory Neurons - Borbély, Éva; Hunyady, Ágnes; Pohóczky, Krisztina; Payrits, Maja; Botz, Bálint; Mócsai, Attila; Berger, Alexandra; Szőke, Éva; Helyes, Zsuzsanna (Frontiers in Pharmacology, 2021)
The tachykinin hemokinin-1 (HK-1) is involved in immune cell development and inflammation, but little is known about its function in pain. It acts through the NK1 tachykinin receptor, but several effects are mediated by a yet unidentified target. Therefore, we investigated the role and mechanism of action of HK-1 in arthritis models of distinct mechanisms with special emphasis on pain. Arthritis was induced by i.p. K/BxN serum (passive transfer of inflammatory cytokines, autoantibodies), intraarticular mast cell tryptase or Complete Freund’s Adjuvant (CFA, active immunization) in wildtype, HK-1- and NK1-deficient mice. Mechanical- and heat hyperalgesia determined by dynamic plantar esthesiometry and increasing temperature hot plate, respectively, swelling measured by plethysmometry or micrometry were significantly reduced in HK-1-deleted, but not NK1-deficient mice in all models. K/BxN serum-induced histopathological changes (day 14) were also decreased, but early myeloperoxidase activity detected by luminescent in vivo imaging increased in HK-1-deleted mice similarly to the CFA model. However, vasodilatation and plasma protein extravasation determined by laser Speckle and fluorescent imaging, respectively, were not altered by HK-1 deficiency in any models. HK-1 induced Ca2+-influx in primary sensory neurons, which was also seen in NK1-deficient cells and after pertussis toxin-pretreatment, but not in extracellular Ca2+-free medium. These are the first results showing that HK-1 mediates arthritic pain and cellular, but not vascular inflammatory mechanisms, independently of NK1 activation. HK-1 activates primary sensory neurons presumably via Ca2+ channel-linked receptor. Identifying its target opens new directions to understand joint pain leading to novel therapeutic opportunities.